ISCU-p53 axis orchestrates macrophage polarization to dictate immunotherapy response in esophageal squamous cell carcinoma - Jialiang Luo; Xu Zhang; Zhicheng Liang; WeiTao Zhuang; Mingxin Jiang; Min Ma; Shuying Peng; Shujie Huang; Guibin Qiao; Qingyun Chen (Cell Death and Disease)
Abstract Immunological heterogeneity in esophageal squamous cell carcinoma (ESCC) poses a significant challenge to the efficacy and response to immunotherapy. In this study, we used single-cell RNA sequencing to uncover substantial heterogeneity in the tumor microenvironments (TMEs) among patients received PD-1 inhibitor with partial response (PR), stable disease (SD), and that who underwent surgery without prior therapy. Notably, tumors classified as SD demonstrated an immunosuppressive environment, characterized by a higher prevalence of M2-like macrophages and lower frequencies of T and B cells, especially PD1highCD8+ T cells. These PD1highCD8+ T cells were found to frequently engage with macrophages within the TMEs. Focusing on macrophages, we observed elevated expression of the Iron-Sulfur Cluster Assembly Enzyme (ISCU) in macrophages infiltrating SD tumors. ISCU was identified as a promoter of M2 macrophage polarization in a p53-dependent manner. Mechanistically, ISCU sequestrates p53 in the cytoplasm, reducing its nuclear location and relieving transcriptional repression of xCT and Arg1. Consequently, the increased expression of xCT and Arg1 modulates macrophage sensitivity to ferroptosis and the arginine metabolic pathway, thus affecting macrophage differentiation and inflammatory responses. Furthermore, inhibition of ISCU expression was found to repolarize macrophages, enhance CD8+ T cell cytotoxicity, and boost the efficacy of anti-PD-1 antibody. Collectively, our findings highlight the complex interplay within ESCC TMEs and suggest that targeting ISCU might be a novel strategy to reprogram the immunosuppressive TME, potentially improving immunotherapy outcomes in ESCC patients. Schematic illustration of the mechanism by which ISCU facilitates M2 macrophage polarization. ISCU interacted with p53, promoting its retention in the cytoplasm during M2 macrophage polarization. This nuclear reduction of p53 results in the upregulation of xCT and Arg1, as both are negatively regulated at the transcriptional level by p53. The increased expression of xCT and Arg1 modulates macrophage sensitivity to ferroptosis and the arginine metabolic pathway, respectively, thus affecting macrophage differentiation and inflammatory responses. The graphical abstract was created with BioRender.com.